Heart failure therapy: drugs, genes or stem cells?. (September 2013) - Harding, Sian
Professor Sian Harding talks to Caroline Telfer, Assistant Commissioning Editor. Professor Sian Harding obtained her PhD in Pharmacology from King's College, London (UK) in 1981. She became Professor of Cardiac Pharmacology at the National Heart and Lung Institute, a division of the Imperial College Faculty of Medicine, in 2002. Her work has been funded by the British Heart Foundation, the Wellcome Trust, the Medical Research Council, the Biochemical and Biophysical Research Council, the The National Centre for the Replacement, Refinement and Reduction of Animals in Research, Pfizer, GlaxoSmithKline and SmithKline Beecham. Harding is former president of the European Section of the International Society for Heart Research and has organized international cardiovascular science meetings for this society, as well as for the European Society of Cardiology. She is the principal investigator for the first UK gene therapy trial aimed at improving cardiac contractility, organized jointly at Harefield and Papworth Hospitals. Harding is a member of the Nuffield Council on Bioethics and the Medical Research Coucil Regenerative Medicine Research Committee, and Director of a recently awarded British Heart Foundation Cardiovascular Regenerative Medicine Centre. She has been elected Fellow of the American Heart Association, European Society of Cardiology, International Society for Heart Research, Society of Biology and British Society of Pharmacology.